Improved survival of advanced melanoma patients receiving immunotherapy with concomitant antithrombotic therapy: a multicenter study on 2419 patients from the prospective skin cancer registry ADOReg - Kött, Julian; Zell, Tim; Zimmermann, Noah; Rünger, Alessandra; Smit, Daniel Jan; Abeck, Finn Frederik; Geidel, Glenn; Hansen-Abeck, Inga; Heidrich, Isabel; Weichenthal, Michael; Ugurel, Selma; Leiter-Stöppke, Ulrike; et al. (European journal of cancer, 2025)
Background - Cancer immunotherapy has revolutionized melanoma treatment, but the high number of non-responders still emphasizes the need for improvement of therapy. One potential avenue for enhancing anti-tumor treatment is through the modulation of coagulation and platelet activity. Both have been found to play an important role in the tumor microenvironment, tumor growth and metastasis. Preclinical studies indicate a beneficial effect, clinical data has been inconsistent. - Methods - We examined a cohort of advanced, non-resectable melanoma patients (n = 2419) derived from the German prospective multicenter skin cancer registry ADOReg, who were treated with immune checkpoint inhibitors (ICI). The patients were classified based on whether it was documented that they received platelet aggregation inhibition (PAI) (n = 137) (acetylsalicylic acid (ASA) or clopidogrel), anticoagulation (AC) (n = 185) (direct oral anticoagulation (DOAC), phenprocoumon, heparins) at the start of ICI or no antithrombotic medication (n = 2097) at any point during ICI treatment. The study endpoints were best overall response (BOR), progression-free survival (PFS) and overall survival (OS). - Results - A significantly improved PFS was observed in patients documented to receive ASA (15.1 vs 6.4 months, HR 0.67, 95 % CI: 0.5 to 0.88, p = 0.0047) as well as in patients to receive AC (15.1 vs. 6.4 months, HR 0.7, 95 % CI: 0.53 to 0.91, p = 0.01) compared to patients for whom no antithrombotic medication was documented. Multivariate analysis of OS showed significant risk reduction in patients who received DOAC (HR 0.68, 95 % CI: 0.49 to 0.92, p = 0.0170) or phenprocoumon (HR: 0.44, 95 % CI: 0.19 to 0.85, p = 0.0301). - Conclusion - Our study indicates a positive prognostic effect of anticoagulant and antiplatelet concomitant medication in melanoma patients receiving ICI. Further studies are needed to confrim the cancer-related benefit of adding anticoagulation or platelet inhibition to ICI treatment.
Online verfügbar: 30. November 2024, Artikelversion: 5. Dezember 2024
Gesehen am 08.05.2025